The role of Pharmaceutical Marketing in Prescribing Decisions in a Developing Country: A Comprehensive Study Exploiting Theory of Planned Behaviour - Mahmoud Al-Areefi; Mohamed Izham Mohamed Ibrahim; Abubakr Abdelraouf Alfadl (Journal of Public Health and Pharmacy)
Background: Prescription medicines have become a major component of health systems in both developed and developing countries contributing to, may be, more than half of the total health care expenditure in the developing countries. Although literature directly attributing rise in medicines expenditure to prescribers’ decision, but still only a few researches had employed studies with sound theoretical foundations to comprehensively examine prescribing decision behaviours. Our objective was to investigate potentially modifiable factors, which may influence prescribing decisions of physicians employing theory of planned behaviour.